The associations between optimism, personal growth initiative and the latent classes of social media addiction - Yue, Heng; Gao, Shiwen; Huang, Yufeng; Zhang, Xuemin (Frontiers in Psychology, 2025)
Most previous studies have explored the risk antecedents of social media addiction, while few studies have focused on the protective factors that may decrease the risk of this behavioral disorder. By using a person-centered method, the current study focused on the effects of two protective factors (optimism and personal growth initiative) on the latent classes of social media addiction. 552 college students (248 females) participated in the current study, Mplus 8.3 software was adopted to conduct the latent class analysis.The results revealed that based on the scores of the Bergen Social Media Addiction Scale, social media users were classified into three subgroups: low-risk class, moderaterisk class, and high-risk class. The prevalence rate of social media addiction in college students was about 9.6%. Female gender was a positive predictor of the membership of a higher-risk class. Individuals with greater optimism and personal growth initiative were less likely to be classified in a higher-risk class.